Reconsidering Digital Text Interpretation: A Dialogical Engagement Between Derrida’s Deconstruction and Gadamer’s Hermeneutics - Husaini Nasution; Eva Dewi; Rasalhaque Daffa Taruna (Refleksi: Jurnal Kajian Agama dan Filsafat, 2025)
This article examines a dialogical epistemological engagement between Jacques Derrida’s deconstruction and Hans-Georg Gadamer’s philosophical hermeneutics as a theoretical approach to interpreting contemporary digital texts. The digital era is characterized by fluid, multimodal, fragmented, and algorithmically mediated texts, which challenge classical assumptions about meaning, language, and interpretation. Derrida’s deconstruction emphasizes the instability of meaning through the concept of différance, highlighting the continual deferral and relational movement of meaning within networks of signs. In contrast, Gadamer’s hermeneutics underscores the role of productive prejudice, wirkungsgeschichte (history of effects), and the fusion of horizons in the process of understanding. Through philosophical and library-based research, this study demonstrates that despite their apparent differences, Derrida and Gadamer share important epistemological assumptions, including the non-finality of meaning, the centrality of language, the active role of the interpreter, and the relational positioning of texts. This dialogical engagement is proposed as an interpretive framework referred to as “Digital Deconstructive Hermeneutics,” which is relevant for interpreting digital texts shaped by rapid change, intertextuality, and algorithmic mediation. The findings contribute to contemporary debates on interpretive epistemology in the digital age and offer insights for digital literacy and cultural studies.